Investigating the Effect of the Traditional Flipped Classroom in Teaching Primary 3 Class Mathematics - Sulaimon, Jamiu Temitope; Manditereza, Blandina (Journal of Education and Practice, 2024)
Purpose: The purpose of the study is to investigate how the "flipped" classroom impacts Primary 3 Mathematics students' learning and achievement. Methodology: In this study, mathematics instruction in Primary 3 was recontextualised using the Flipped Classroom methodology. Using pre- and post-test methodology, a quasi-experimental research design was used with 81 lower essential school students from two private primary schools. Data collection utilised three designed instruments: the Mathematics Achievement Test (MAT), Traditional Flipped Classroom Instructional Guide (TFCIG), and Control Group Instructional Guide (CGIG). The test-retest reliability of MAT was established at 0.75. The study explored the potential benefits of the flipped classroom model in improving pupils' mathematics achievement and interest within the three primary classes. Two hypotheses were formulated and analysed using descriptive statistics for demographics and Analysis of Covariance (ANCOVA) at a 0.05 significance level. Findings: The findings shed light on the success of using a flipped model to recontextualise math classes at the Primary 3 level in Mathematics in Ilorin South Local Government Area of Kwara State, Nigeria. The findings indicate a significant positive effect of traditional flipped classroom instructional strategy on pupils' academic achievement in Mathematics. However, there was no significant interaction effect between treatment and gender. The conclusion is that the traditional flipped classroom instructional strategy improves pupils' academic achievement, irrespective of gender. This study found a statistically significant effect size for the flipped classroom instructional strategy. Unique Contributions to theory, policy and practice: This research contribution is twofold. Firstly, the study advances our understanding of the advantages, difficulties, and prospective improvements of flipped learning in Mathematics classes in Primary schools. Secondly, this study helps teachers understand how to integrate the flipped classroom within the learning and teaching system. The study recommends that school teachers or educators undergo training to implement traditional flipped classroom instructional strategies in math classes effectively.